Wyzwania współczesnego przywództwa kierowniczego - Wiśniewska-Szałek, Agata (The Challenges of Modern Leadership, 2008)
This article is an attempt to present the changes occurring in leadership of global societies in the generation. In the first part the terms of postmodernism and globalization are evaluated, with the second one considered to be one of key characteristics describing generation next world. It also points out the changes that took place in the social aspect and economic system. In the second part of the article the pressure is put on the way these changes affect the manager's leadership work as well as on the referral to overall tendencies appearing in the leadership of a XXI-century company. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 253-263